Knowledge level of farmers vis-à-vis improved sugarcane production technology in Lakhimpur Kheri district, Uttar Pradesh - Ranjeet Kumar; N.R. Meena; R.K. Doharey; Avneesh Kumar; Sandeep; Kamni Paia Biam; Amit Kumar (Annals of Agricultural Research, 2025)
India, being the second-largest producer, considers sugarcane vital not only for sugar production but also for its role in generating bio-products and supporting agro-based industries. Despite its significance, the sector faces challenges, including limited farmer awareness of improved production technologies. This study was conducted during 2022-23 in Lakhimpur Kheri district of Uttar Pradesh—one of the major sugarcaneproducing regions in the state—with the objective of assessing the knowledge level of farmers regarding improved sugarcane production technologies and identifying factors influencing this knowledge. A total of 120 farmers from Bankeyganj and Kumbhigola blocks were selected through proportionate random sampling. Data were collected using a pre-structured interview schedule and analyzed using suitable statistical tools. The findings revealed that the majority of farmers possessed a medium level of knowledge, with the highest awareness in practices such as ratooning, sowing time, and water management. Correlation analysis showed that variables such as education, land holding, type of family, risk orientation, economic motivation, and scientific orientation had a highly significant and positive relationship with knowledge levels. In contrast, caste, annual income, family size, social participation, and age were negatively correlated, with the latter two showing high significance. Marital status, material possessions, and extension contact were found to be non-significant but positively correlated. These insights highlight the critical socio-economic and psychological factors that influence the dissemination and adoption of improved sugarcane cultivation practices and suggest the need for targeted extension efforts to bridge knowledge gaps among farmers.